Systems biology. - Rigoutsos, Isidore; Stephanopoulos, G. (Series in systems biology., 2007)
1. Mass Spectrometry in Systems Biology 3, Cristian I. Ruse & John R. Yates III. 2. Mathematical Modeling and Optimization Methods for De Novo Protein Design 42, C.A. Floudas & H.K. Fung. 3. Molecular Simulation and Systems Biology 67, William C. Swope, Jed W. Pitera, & Robert S. Germain. 4. Global Gene Expression Assays: Quantitative Noise Analysis 103, G.A. Held, Gustavo Stolovitzky, & Yuhai Tu. 5. Mapping the Genotype-Phenotype Relationship in Cellular Signaling Networks: Building Bridges Over the Unknown 137, Jason A. Papin, Erwin P. Gianchandani, & Shankar Subramaniam. 6. Integrating I.